The Impact of Workplace Ostracism Induced by Co-Worker Envy on Psychological Empowerment and Organizational Commitment - Risgiyanti; Joko Suyono; Harmadi; Suryandari Istiqomah (Faculty of Economics and Business, Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: Ostracism is a painful workplace experience that may influence employees' attitudes and behavior. This study aims to analyze how workplace ostracism impacts employees’ psychological empowerment and commitment through the co-worker envy mechanism. Background Problems: Previous studies mostly focused on ostracism and its effect on employees and organizations, and demonstrated inconsistency concerning the relationship between it and commitment. Novelty: The current study fills a gap, namely the inconsistencies of previous studies into the direct effect of workplace ostracism on organizational commitment. Research Methods: Data were collected from employees in the information and communication technology sectors in Indonesia. To collect the data, we used a self-report questionnaire to assess the employees’ perceived co-worker envy, perceived workplace ostracism, psychological empowerment, and commitment. Out of 499 online survey questionnaires filled out by the respondents, 201 responses met the criteria. Partial least squares structural equation modelling (PLS-SEM) was used to test the proposed hypotheses. Findings/Results: The result indicates that co-worker envy positively influences workplace ostracism. The resulting workplace ostracism indirectly leads to lower commitment, via employee psychological empowerment as a mediator. Conclusion: Taken together, the results of the study give additional and more substantial empirical evidence to the workplace ostracism literature.